2021
DOI: 10.3390/jpm11040252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP3A5 Polymorphism on Rapid Progression of Chronic Kidney Disease: A Prospective, Multicentre Study

Abstract: Personalised medicine is potentially useful to delay the progression of chronic kidney disease (CKD). The aim of this study was to determine the effects of CYP3A5 polymorphism in rapid CKD progression. This multicentre, observational, prospective cohort study was performed among adult CKD patients (≥18 years) with estimated glomerular filtration rate (eGFR) ≥30 mL/min/1.73 m2, who had ≥4 outpatient, non-emergency eGFR values during the three-year study period. The blood samples collected were analysed for CYP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Venous blood was collected from patients and DNA was extracted using the DNeasy ® Blood and Tissue extraction kit (Qiagen, Hilden, Germany). A polymerase chain reaction of the region encompassing the CYP3A5*3 gene polymorphism was performed using the TopTaq Mastermix Kit (Qiagen, Hilden, Germany), followed by direct sequencing using the BigDye ® Terminator version 3.1 cycle sequencing kit, which was run on a 96-capillary 3730xl DNA Analyzer (developed by Applied Biosystem, United States and produced by Thermo Fisher Scientific) ( Boutin et al, 2000 ; Lee et al, 2021a ). Other gene polymorphisms of the CYP3A5 gene were not assessed, given the low prevalence of other polymorphisms in South East and East Asian populations ( Dorji et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Venous blood was collected from patients and DNA was extracted using the DNeasy ® Blood and Tissue extraction kit (Qiagen, Hilden, Germany). A polymerase chain reaction of the region encompassing the CYP3A5*3 gene polymorphism was performed using the TopTaq Mastermix Kit (Qiagen, Hilden, Germany), followed by direct sequencing using the BigDye ® Terminator version 3.1 cycle sequencing kit, which was run on a 96-capillary 3730xl DNA Analyzer (developed by Applied Biosystem, United States and produced by Thermo Fisher Scientific) ( Boutin et al, 2000 ; Lee et al, 2021a ). Other gene polymorphisms of the CYP3A5 gene were not assessed, given the low prevalence of other polymorphisms in South East and East Asian populations ( Dorji et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…For ACEIs and ARBs, there was no influence of CYP3A5*3 on pharmacogenetics in CKD ( Lee et al, 2021 ).…”
Section: Influence Of Gene Polymorphisms On Response To Raas Inhibitionmentioning
confidence: 99%
“…These studies [12][13][14] also demonstrated the modifiable factors associated with CKD which included alcohol consumption, overweight, obesity, prediabetes, diabetes mellitus and hypertension. Studies conducted in Malaysia also examined the non-modifiable [15], modifiable [7] factors and the interactions between these factors [16] with CKD. One modifiable factor is knowledge, and it is agreed that knowledge is a crucial step towards preventing a disease [17,18].…”
Section: Introductionmentioning
confidence: 99%